ANALISIS PEMATUHAN DAN PELANGGARAN PRINSIP KERJA SAMA DALAM NOVEL GENTA DAN NANDEA KARYA KATA KOKOH: Array - Ilma, Chamalatul; Setyorini, Ririn (Universitas Peradaban, 2022)
This study aims to describe and analyze: (1) the form of compliance with the principle of cooperation found in the novel Genta dan Nandea by Kata Kokoh, (2) the form of violation of the principle of cooperation found in the novel Genta dan Nandea by Kata Kokoh. This research is a type of qualitative research using a pragmatic approach. The data of this study is in the form of excerpts of dialogues of characters in the novels Genta dan Nandea, which are indicated to contain compliance and violations of the principle of cooperation. The source of this research data is the novel Genta dan Nandea by Kata Kokoh. The data collection technique uses the technique of assessing the content of the document. The data analysis technique uses Miles and Huberman model analysis, which includes the process of data collection, data reduction, data presentation, and conclusion drawing/verification. The results showed: (1) there were 88 forms of compliance with the principle of cooperation in Genta dan Nandea novels, including quantity maxims, quality maxims, relevance maxims, and implementation maxims. (2) there were 50 forms of violation of the principle of cooperation in Genta dan Nandea novels consisting of quantity maxims, quality maxims, relevance maxims, and implementation maxims.